The trade effects of anti-dumping duties, non-tarif barriers and maritime security: Gravity applications - Alexander-Nikolai Sandkamp (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2020)
This dissertation was prepared by Alexander-Nikolai Sandkamp, completed in September 2018 and first published online by LMU Munich in February 2019. It consists of four selfcontained chapters that empirically investigate different trade dampening phenomena using gravity analysis. The first two chapters examine the effects of anti-dumping duties on trade, addressing endogeneity concerns linked to trade policy. In particular, Chapter 1 exploits the EU enlargement of 2004 as a natural experiment to analyse trade effects of European anti-dumping duties across different exporting countries. Chapter 2 examines the universe of Chinese firm-level exports to identify trade effects across different importing countries. Chapter 3 investigates how the implementation of non-tarif barriers reduces bilateral imports. Finally, Chapter 4 uses Chinese customs data to examine the impact of maritime piracy on Chinese export flows as well as firms' choice of transport mode.
Keywords: F12; F13; F14; F19; D22; N70; R41; 330; Trade; Anti-Dumping; European Union; China; Non-Tarif Barriers; Gravity; Transport; Piracy; Market Economy Status; Firm Heterogeneity